1969
DOI: 10.1021/j100844a052
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of aqueous nitrate solutions excited in the 195-nm band

Abstract: The photochemistry of aqueous nitrate solutions excited in the high-energy (195-nm) mr* band of the ion is investigated using steady-state and flash-irradiation techniques. The formation of hydroxyl radicals is demonstrated by observing the absorption of characteristic transients formed by the reaction of O H (or 0-) with C082-, CNS-, and 02. T h e formation of pernitrite is also investigated and found t o be unaffected by [NO2-], [NOI-], [02], and [CH,CH20H]. The flash technique enables the determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 0 publications
2
40
2
1
Order By: Relevance
“…The positive influence of the humic acids on the conversion of nitrate could have its origin in the increase of the pH upon addition of the humic acids. Other authors [3,6,31] observed an increase in the rate of formation of nitrite with increased pH. It is not possible to distinguish from our data whether the effect of the humic acids is a consequence of the change in pH, or of reactive species formed from humic acids under irradiation, i.e.…”
Section: Humic Acids and Nitratecontrasting
confidence: 87%
See 2 more Smart Citations
“…The positive influence of the humic acids on the conversion of nitrate could have its origin in the increase of the pH upon addition of the humic acids. Other authors [3,6,31] observed an increase in the rate of formation of nitrite with increased pH. It is not possible to distinguish from our data whether the effect of the humic acids is a consequence of the change in pH, or of reactive species formed from humic acids under irradiation, i.e.…”
Section: Humic Acids and Nitratecontrasting
confidence: 87%
“…Kudo et al [18] irradiated 1M NaNO 3 and 1M HNO 3 , respectively, in experiments similar to ours and observed the formation of nitrite with a rate of 0.3 µmol/h in both cases. An increasing rate of formation of nitrite with increasing pH in the range of 5 to 8 was reported by Daniels [5], Wagner [6], Warneck [7], and Shuali [31]. Photoreduction of nitrate to nitrite has also been applied for the quantitative analysis of nitrate [32,33], with an increased reduction efficiency at increased pH.…”
Section: Photoinduced Reduction Of Nitratementioning
confidence: 82%
See 1 more Smart Citation
“…From this result we can confirm that 254 nm of wavelength emitted from the Hg-lamps may excite nitrate ions. In this regard, similar results have been described elsewhere[6,[10][11][12]. Thus, the rapid dissolution of U0 2 in the presence of…”
supporting
confidence: 88%
“…Dans le processus de photolyse des nitrates, les nitrites ne sont pas les seules espèces produites. La présence de radicaux OH* et NO2* a été démontrée par analyse spectroscopique (21). Des travaux plus récents ont montré que la production de radicaux OH' dans les eaux de surface était principalement provoquée par une photolyse lente des ions nitrates (23)(24).…”
Section: Discussionunclassified